1984
DOI: 10.1159/000241756
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Response to Tilting in Newborns in Quiet and Active Sleep

Abstract: The heart rate response to tilting was investigated in active and quiet sleep in 19 normal newborns (age 1–7 days) and 11 healthy premature infants (age 2–19 days). RR intervals were determined by computer from the ECG for 30–60 s periods immediately before and after each tilt. Term infants had a significant (p < 0.005) decrease in RR interval for head-up tilting and significant (p < 0.005) increase in RR with head down tilts. There was no significant difference in the magnitude of RR change between upward and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Following the head-up tilt, the stable HR response was very strongly associated with sleep state, both with and without movement in the analysis. In contrast, studies of preterm and term infants slowly tilted head-up to 30°or 60°( so as not to induce sighs or movement), found no association between the stable heart rate change and sleep state (24,25).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Following the head-up tilt, the stable HR response was very strongly associated with sleep state, both with and without movement in the analysis. In contrast, studies of preterm and term infants slowly tilted head-up to 30°or 60°( so as not to induce sighs or movement), found no association between the stable heart rate change and sleep state (24,25).…”
Section: Discussionmentioning
confidence: 91%
“…We found the ratio measure to be higher in older infants suggesting a larger reflex response to the tilt, findings that were reproduced by defining the profile of the response but not apparent once the heart rate reached a stable level. However with a rapid tilt, sighs, apneas, and movement are common and some stress the importance of measuring heart rate responses only in the absence of these (24,25). By excluding movement in our analysis, the maturational effect remained for the reflex response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recordings made after infants were allowed to settle at least 3-5 min in HETP did not reveal significant changes in heart rate and blood pressure. Conflicting data in the heart rate response of preterm infants to positional changes in former studies resulted mainly from different time schedules during evaluation and different ages of populations [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…In the latter study, blood pressure was also unchanged on tilting however peripheral vascular resistance increased significantly, and there was no correlation between cardiovascular parameters and gestational or chronological age (Lagercrantz et al, 1990). In contrast, Finley et al, (Finley et al, 1984) showed that both term infants studied in the first week after birth and preterm infants (born at 33 -37 week GA) studied at 2 -29 d had significant increases in heart rate on head-up tilting (30) and significant decreases on head-down tilting, results were however very variable between infants. In addition, there was no difference in responses between sleep states, and they concluded that control of heart rate was well developed at term.…”
Section: Baroreflex Control Of Heart Rate and Blood Pressurementioning
confidence: 70%